2015
DOI: 10.1371/journal.pone.0119788
|View full text |Cite
|
Sign up to set email alerts
|

Determining Microvascular Obstruction and Infarct Size with Steady-State Free Precession Imaging Cardiac MRI

Abstract: PurposeIn cardiac MRI (cMRI) injection of contrast medium may be performed prior to the acquisition of cine steady-state free precession (SSFP) imaging to speed up the protocol and avoid delay before late Gadolinium enhancement (LGE) imaging. Aim of this study was to evaluate whether a condensed clinical protocol with contrast cine SSFP imaging is able to detect early microvascular obstruction (MO) and determine the infarct size compared to the findings of LGE inversion recovery sequences.Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…It is challenging to accurately quantify the heterogeneity of small low-signal areas on LGE images, which requires experienced radiologists and much analysis time and is not conducive to widespread clinical application, especially in some non-highly specialized centers. However, MVO can be detected with contrast cine SSFP imaging ( 11 ). In our study, MVO was identified in 109 (51%) patients using CE-cine SSFP imaging and 107 (50%) in LGE imaging, comparable to LGE, CE-cine can serve as a backup when LGE imaging is unavailable ( 10 , 11 ) and can shorten scanning time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is challenging to accurately quantify the heterogeneity of small low-signal areas on LGE images, which requires experienced radiologists and much analysis time and is not conducive to widespread clinical application, especially in some non-highly specialized centers. However, MVO can be detected with contrast cine SSFP imaging ( 11 ). In our study, MVO was identified in 109 (51%) patients using CE-cine SSFP imaging and 107 (50%) in LGE imaging, comparable to LGE, CE-cine can serve as a backup when LGE imaging is unavailable ( 10 , 11 ) and can shorten scanning time.…”
Section: Discussionmentioning
confidence: 99%
“…However, MVO can be detected with contrast cine SSFP imaging ( 11 ). In our study, MVO was identified in 109 (51%) patients using CE-cine SSFP imaging and 107 (50%) in LGE imaging, comparable to LGE, CE-cine can serve as a backup when LGE imaging is unavailable ( 10 , 11 ) and can shorten scanning time. Therefore, MVO identification from CE-SSFP can be sufficient for clinical application, and it has a high degree of completion and accuracy, can be an option in patients who are limited in their ability to comply with the demands of a CMR protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Figura 5.16 reforça a separação das classes a partir dos valores expressos em todos os atributos analisados entre os padrões de fibrose para CINE-RMC e RT-RMC. O padrão de fibrose focal é representado na figura como o destaque na distinção com os demais padrões, embora seja mais evidente sua diferença na análise por RT-RMC quando comparada com a análise por CINE-RMC.No estudo realizado por Wuest[89], foi avaliada a aplicação do contraste gadolínio antes da aquisição de imagens CINE em pacientes com infarto miocárdico. Heatmap referente aos valores obtidos para cada atributo em relação ao miocárdio segmentado em imagens CINE-RMC de 60 pacientes com CCC para as porções apical, médio cavitário e basal.Figura 5.15: Heatmap referente a matriz de auto correlação e correlações cruzadas entre os valores dos 96 atributos analisados em CINE-RMC.…”
unclassified